Pandangan Gereja Katolik Tentang Pendidikan Anti Kekerasan dan Implementasinya Bagi Kehidupan Gereja - Paulus JD Lohor; Hilario Didakus Nenga Nampar (Sekolah Tinggi Kateketik Pastoral Katolik (STKPK) Bina Insan Keuskupan Agung Samarinda, 2021)
This study aims to study the views of the Catholic Church on anti-violence education and find forms of anti-violence education. This study uses a literature review approach to collect data from various journal articles, books, documents and various sources related to anti-violence education. The collected data was then analyzed descriptively. The results of the study show that the Catholic Church's view of violence is a form of moral crime and an act that does not respect the human person. Therefore, the Catholic Church firmly rejects acts of violence against humans in any form. Forms of anti-violence education that can be carried out in schools, families, and the general public are such as conducting socialization about the dangers of bullying behaviour, providing religious education to improve the moral quality of students, active non-violent movement activities. The existing anti-violence education is a concrete manifestation of the role of the Catholic Church in calling for the importance of anti-violence education. It is also intended to create a harmonious relationship with others.